THE ROLE OF BUSINESS INCUBATORS AND INNOVATION MANAGEMENT IN INCREASING THE PERFORMANCE OF SMEs IN INDRAMAYU REGENCY - Agus Yudianto; Meddy Nurpratama (BBM (Buletin Bisnis & Manajemen), 2023)
Objectives The role of the innovation management business incubator towards the process of innovation and change management towards marketing performance. This type of research is "explanatory research", with the aim of explaining the relationship between research variables, especially in the context of causality. This research tests hypotheses and involves description, but the main focus is on the relationships between variables. The variables studied include the creation, existence, modification of all resources used in innovation, innovative performance, and sustainable competitive advantage. In this study, calculations were carried out using F count with a significance level of 5%. The calculation results obtained an calculated F value of 6,400, with a degree of freedom of 27. The obtained F table value was 3.354. In addition, the significance value obtained is 0.005, which is smaller than the specified level of significance. This shows that simultaneously (together), the independent variables of the MSME Incubator and Innovation Management have a significant effect on MSME performance